VMP1 promotes exosome secretion and enhances 5-FU resistance in colon cancer cells. (August 2022) - Wei, Xueni; Yang, Zhonghui; Chen, Guomei; Huang, Ji
Abstract: Background: Drug resistance of colon cancer cells is the key to affect the efficacy of colon cancer chemotherapy and lead to chemotherapy failure. Recent studies have found that exosomes play an important role in chemoresistance of colon cancer, while the expression of VMP1 may be involved in exosome secretion. Method: Drug sensitivity of colon cancer cells was detected by MTT. VMP1 expression levels were detected by qPCR and western blot. Expression of VMP1 was silenced in SW620 and HT-29 cell lines. Exosomes were isolated by ultracentrifugation, the particle size and concentration of exosomes were analyzed by NTA, and the morphology of exosomes was investigated by transmission electron microscopy. Exosome marker protein expression was detected by Western blot. The effect of exosomes on 5-FU sensitivity in SW620 and HT-29 cells was examined by MTT and western blot. Results: VMP1 presented high expression in SW620 and HT-29 cells, their VMP1 gene and protein levels were significantly higher than those in SW480 and HCT116 cells, they were less sensitive to 5-FU, and exosome secretion was significantly reduced in SW620 and HT-29 cells after silencing of VMP1. Importantly, addition of exosomes to cells after silencing of VMP1 re-improved drug resistance. Co-incubation of exosomes secreted from SW620 and HT-29 cells with homologous cells significantly increased cell viability after 5-FU (50 μM) treatment, and increased the expression levels of the resistance protein ABCC1 and the anti-apoptotic protein Bcl-2. Conclusion: High expression of VMP1 in colon cancer cells is able to promote exosome secretion, which mediates the acquisition of more drug-resistant properties by cancer cells. Highlights: VMP1 is highly expressed in colon cancer cells. VMP1 promotes exosome secretion. VMP1 enhances 5-FU resistance.